Effect of dietary vitamin A against the toxic effect of afiatoxin B, on the cytochrome P450 in the liver microsomal protein of Rattus norvegicus rats - Wiryatun Lestariana, Wiryatun Lestariana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Liver cytochrome P450 microsomal protein metabolizes certain xenobiotic compounds into reactive intermediates which covalently bind to DNA, RNA or protein of nucleus. The action of cytochrome P450 can be Influenced by nutrition status and environmental pollution. Aflatoxin Bi (AFB) is the environmental exposure problem in the countries with tropical climate. Aflatoxin Ell can also be oxidized by cytochrome P450 to DNA and protein - binding metabolites and can give rise to cell injury, mutation and cancer. The objective of this study is to Investigate the effect of dietary vitamin A (deficient, adequate, fourfold-adequate) against the toxic effect of AFBi in the liver cytochrome P450 microsomal protein of rats. Variance analysis of the result showed that the interaction of the vitamin A in the diet and treatment with AFB, had no significant effect. However the rats with dietary deficient and adequate in vitamin A, treated with AFBi showed significantly increased the cytochrome P450 (p< 0.001 I. The dietary fourfold-adequate in vitamin A was able to maintain the concentration of cytochrome P450 in liver microsomal protein of rats treated with AFB1 within normal range. It Is concluded that the effect of dietary vitamin A against the toxic effect of AFB, in liver cytochrome P450 microsomal protein of rats depends on the vitamin A concentrations in the diet consumed.Keywords: dietary vitamin A - aflatoxin Bt - liver microsomal protein - cytochrome P450 - Rattus norvegicus